Innovation of Aromatherapy Product using Aceh Essential Oil - Syaifullah Muhammad; M. Dirhamsyah; Ernawati Ernawati; Raihan Dara Lufika; Sabrina Khairunnisa; Nanda Funna Ledita (Universitas Syiah Kuala, 2022)
Nowadays, many Indonesian people return to various traditional medicinal plants to cure various diseases. This is due to the development of various sciences and technology, one of which is in the Atsiri field. Essential oils are often used as aromatherapy because they can foster a feeling of calm and can keep away from feelings of anxiety and restlessness. The use of essential oils from spices is a suitable choice of innovation in today's modern world of health. The purpose of this research is to make aromatherapy products using high-grade patchouli oil and essential oils of Acehnese spices that are efficacious for treating various diseases. The ingredients used in the manufacture of this product are high-grade patchouli oil, cajuput oil, nutmeg oil, cinnamon oil, clove bud oil, menthol, champers, and carrier oil. The research stage was started by developing the aromatherapy formulas, establishing the working procedures, and conducting quality testing. This spice aromatherapy product was tested on 25 respondents to determine its effectiveness on health. The results show that 68% respondents agree that spice aromatherapy products can affect body relaxation and 55% agree that they can improve sleep quality. As many as 88% of respondents agree that spice aromatherapy is effective for reducing headaches and catching colds and 84% of respondents agree that this product has an effect on relieving breathing. The results also show that all respondents agree that this product has a unique and classic aroma. However, there are some respondents (28%) who do not like this scent, while 72% really like it. These results show that spice aromatherapy products still need to be formulated to get other aroma variants to provide an alternative for consumers who do not like the strong aroma of spices.